Geography, Climate, and Genes in Development Studies - Klitgaard, Robert; Fedderke, Johannes W.; Napolioni, Valerio (Published by Oxford University Press on behalf of the World Bank, 2021)
Over the coming decade, much more genetic data will enter into the study of economic development. This paper provides an example and emphasizes the uses and misuses of such information. It has assembled for the first time national frequencies of the ACP1 genetic polymorphism and the Interleukin-6 (IL6-174G) and Interleukin-10 (IL10-1082G) cytokines. These three respond over the centuries to ultraviolet radiation and infectious diseases. The study also looks at a national measure of heterozygotic diversity. In particular, it finds that ACP1 frequencies are significantly related to national outcomes ranging from GDP per capita to type and quality of governance, to measures of national “competitiveness,” to health, to fertility, to measures of satisfaction with life. These associations do not seem explainable by reverse causation nor by the influence of some of the usual variables in studies of long-run development. Nonetheless, these results do not mean that a few genes have a direct causal effect on world development. The ACP1*B variable is surely picking up the influences of many genetic and cultural adaptations over evolutionary time in response to ultraviolet exposure and pathogen burdens. This study's findings thus support other research indicating the importance of disease environments in shaping both genetic and sociocultural adaptations that have influence on development outcomes today. The paper concludes with a discussion of what such strong associations mean and do not mean, in hopes of guiding future studies of genes and other deep roots of economic development.